Biocontrol of Rhizoctonia solani in basmati rice by the application of Lactobacillus and Weissella spp. - Maira Akhtar; Asia Nosheen; Rumana Keyani; Humaira Yasmin; Rabia Naz; Saqib Mumtaz; Muhammad Nadeem Hassan (Scientific Reports, 2023)
Abstract Rice is a staple food crop and is a major source of employment and income in the world. However, the attack of fungal disease poses a serious threat to the crop growth and productivity and leads toward yield loses. Therefore, current study was performed to evaluate the biocontrol potential of Lactobacillus and Weissella spp. on basmati rice against Rhizoctonia solani. Agar disc method was performed to evaluate the antifungal activity of both bacteria against R. solani. Petri plate and pot experiments were conducted to evaluate the growth promotion and biocontrol potential of both bacteria in Basmati rice under R. solani stress. Results indicated that maximum antifungal activity (82%) was recorded by Lactobacillus sp. Maximum phosphate solubilization and siderophore production was recorded by Weissella sp. In petri plate experiment, maximum root length, root fresh and dry weight (36%, 40% and 13%) was recorded by Weissella sp. and maximum shoot length and shoot fresh weight (99% and 107%) by Lactobacillus sp. In pot experiment, both bacteria enhanced the growth parameters of Basmati rice including root and shoot length, fresh and dry weight as well as no. of lateral roots. Application of Weissella sp. resulted in maximum increase (332% and 134%) in chlorophyll a and b content while Lactobacillus sp. + R. solani showed maximum (42%) carotenoid contents. Lactobacillus sp. + R. solani showed maximum increase in the proline (54%) and sugar contents (100%) while Lactobacillus sp. alone showed maximum (35%) soluble protein contents. Plant defense enzymes i-e SOD (400%), POD (25%), CAT (650%), PPO (14%) and PAL (124%) were notably increased by Weissella sp. + R. solani and Lactobacillus sp + R. solani. The Lactobacillus sp showed the best results in antifungal activity against R. solani and Weissella sp. showed the best results in production of defense enzymes in basmati rice against R. solani stress and can be suggested as the potent biocontrol agents for the rice crop.